Plant‐Based Meat Alternatives Intake and Its Association With Health Status Among Vegetarians of the UK Biobank Volunteer Population - Hana F. Navratilova; Anthony D. Whetton; Nophar Geifman (Food Frontiers)
ABSTRACT Consumption of plant‐based meat alternatives (PBMAs) within the vegetarian population is increasing. This study assessed the relationship between PBMA intake and health markers using the UK Biobank cohort. Participants were categorized into vegetarian PBMA consumers and vegetarian PBMA nonconsumers. Nonparametric statistical tests were used to evaluate differences in participants’ characteristics, food intake, and 30 blood biochemistry measures after assessing data distributions. Metabolomics (168 metabolites) and proteomics (2923 proteins) data were further examined to identify significant differences between the two participant groups. Relative risks (RRs) for 45 chronic diseases and mental conditions were calculated using Poisson regression. Sensitivity analysis accounted for sociodemographic factors, and the proportion of energy from ultra‐processed food (UPF) intake was determined. No substantial differences in sodium, free sugar, total sugar, or saturated fatty acids intake between vegetarian PBMA consumers and nonconsumers were found. However, PBMA consumers exhibited higher blood pressure (130/79 and 129/78 mmHg for consumer and nonconsumer groups, respectively) and elevated C‐reactive protein (CRP) levels (1.76 ± 3.12 and 1.57 ± 3.17 mg/L for consumer and nonconsumer groups, respectively). Metabolite and protein abundance analysis showed no notable differences. Pathway enrichment analysis suggested that PBMAs may influence immune reactions through cell signaling pathways. PBMA consumers had a 42% increased risk of depression (p = 0.03) and a 40% reduction in irritable bowel syndrome (IBS) risk (p = 0.02), compared to nonconsumers. In conclusion, while no clear health risks or benefits were associated with PBMA consumption in vegetarians, the higher risk of depression, elevated CRP, and lower apolipoprotein A levels in PBMA consumers suggest potential inflammatory concerns that warrant further investigation.